MASS SPECTROMETRY OF PROTEINS EXTRACTED FROM PLAQUE-DERIVED CALCIUM PHOSPHATE BIONS - ARSENIY E. Yuzhalin; EVGENIY A. Demidov; SERGEY E. Peltek (Фундаментальная и клиническая медицина, 2018)
Aim. To investigate the proteomic profile of calcium phosphate bions (CPB) derived from atherosclerotic plaques of large human arteries. Materials and Methods. CPB were extracted from femoral atherosclerotic plaques of two patients with coronary artery disease and significant peripheral atherosclerosis utilizing an original protocol. After sodium dodecyl sulfate polyacrylamide gel electrophoresis, we performed tryptic hydrolysis followed by matrix assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS). Mass spectra were identified using the Mascot search engine. Results. Plaque-derived CPB contained bovine and human serum albumin, bovine alpha-2-macroglobulin, and human cytoplasmic actin 1. Hence, we showed that CPB adsorb proteins from both fetal bovine serum and atherosclerotic plaques. Conclusion. Plaque-derived CPB have similar proteomic profile to artificially synthesized CPB, yet adsorbing plaque proteins in addition to those characteristic for the serum.